Adolescents growing with HIV/AIDS: experiences of the transition from pediatrics to adult care - Machado,Daisy Maria (2016)
Abstract The main objective of this work is to describe the formation of the Transition Adolescent Clinic (TAC) and understand the process of transitioning adolescents with HIV/AIDS from pediatric to adult care, from the vantage point of individuals subjected to this process. A qualitative method and an intentional sample selected by criteria were adopted for this investigation, which was conducted in São Paulo, Brazil. An in-depth semi-structured interview was conducted with sixteen HIV-infected adolescents who had been part of a transitioning protocol. Adolescents expressed the need for more time to become adapted in the transition process. Having grown up under the care of a team of health care providers made many participants have reluctance toward transitioning. Concerns in moving away from their pediatricians and feelings of disruption, abandonment, or rejection were mentioned. Participants also expressed confidence in the pediatric team. At the same time they showed interest in the new team and expected to have close relationships with them. They also ask to have previous contacts with the adult health care team before the transition. Their talks suggest that they require slightly more time, not the time measured in days or months, but the time measured by constitutive experiences capable of building an expectation of future. This study examines the way in which the adolescents feel, and help to transform the health care transition model used at a public university. Listening to the adolescents’ voices is crucial to a better understanding of their needs. They are those who can help the professionals reaching alternatives for a smooth and successful health care transition.